2013
DOI: 10.1371/journal.pone.0078962
|View full text |Cite
|
Sign up to set email alerts
|

The Landscape of Inappropriate Laboratory Testing: A 15-Year Meta-Analysis

Abstract: BackgroundLaboratory testing is the single highest-volume medical activity and drives clinical decision-making across medicine. However, the overall landscape of inappropriate testing, which is thought to be dominated by repeat testing, is unclear. Systematic differences in initial vs. repeat testing, measurement criteria, and other factors would suggest new priorities for improving laboratory testing.MethodsA multi-database systematic review was performed on published studies from 1997–2012 using strict inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
353
0
14

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 421 publications
(375 citation statements)
references
References 68 publications
8
353
0
14
Order By: Relevance
“…Approximately 34% of the overall inappropriateness could be attributed to over-utilization. A reliable estimate of inappropriate laboratory testing has recently been provided by a multi-database systematic review, using keywords such as "utilization" and "laboratory test (s)" (8). The pooled results of this meta-analysis showed that the mean rates of overuse and underuse of laboratory testing were as high as 21% and 45%, with overutilization of in vitro diagnostics approximating 44% during initial testing.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 34% of the overall inappropriateness could be attributed to over-utilization. A reliable estimate of inappropriate laboratory testing has recently been provided by a multi-database systematic review, using keywords such as "utilization" and "laboratory test (s)" (8). The pooled results of this meta-analysis showed that the mean rates of overuse and underuse of laboratory testing were as high as 21% and 45%, with overutilization of in vitro diagnostics approximating 44% during initial testing.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] In a survey performed on a random sample of physicians practicing in six high risk specialties, 8 Studdert and colleagues reported that 59% of physicians ordered unnecessary diagnostic tests or procedures due to defensive medicine. Another recent survey of the Italian Agency for Regional Healthcare Systems (Agenzia Nazionale per i Servizi Sanitari Regionali; AGE-NAS) based on over 1500 hospital physicians revealed that 58% of them admitted to practice defensive medicine and, even more importantly, as many as 93% of hospital physicians were not considering of suspending or reducing this practice.…”
Section: Opinion Reportmentioning
confidence: 99%
“…Bu ölçülebilir parametrelerden birisi de gereksiz test istemidir. Gereksiz test isteminin testlerin aşırı kullanımı veya yetersiz kullanımı, gereksiz başlangıç test istemi ve gereksiz test yinelemesi gibi birkaç farklı tipi bulunmaktadır (4) . Prostat kanseri için bir serum belirteci olarak total prostat spesifik antijenin (tPSA) klinik yararı kanıt-lanmış olmasına karşın kusursuz bir belirteç değildir.…”
Section: Introductionunclassified